(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2011)
Many philosophers, beginning with Plato, have classified aesthetic and moral judgments together on the basis of one important, shared feature: both involve value judgments. This practice is misleading, as these two forms of judgment can be very different; for instance, moral judgments always imply obligation and the compulsion to act in certain ways, features that are not necessarily present in aesthetic judgments. This difference has given moral judgments a certain degree of seriousness (Scruton 1974), which implies they must always override other concerns, including aesthetic ones. The difference between moral and aesthetic judgments is, perhaps, most clearly highlighted in the realm of environmental protection. If most of the practical reasons for environmental protection are essentially moral (being geared toward ensuring the survival of present and future generations of humans), then they must override all aesthetic concerns for environmental preservation. How then should we weigh the importance of aesthetic considerations in environmental protection?